Salivary Electrolytes in Patients with Metallic and Ceramic Orthodontic Brackets - Antonija Jurela; Željko Verzak; Vlaho Brailo; Ivana Škrinjar; Karlo Sudarević; Bernard Janković (University of Zagreb. School of Dental Medicine, 2018)
Objectives: It is known from the existing literature that metal ions within orthodontic appliances are prone to corrosion due to the salivary and bacterial interplay in the oral cavity. The results from the most studies show that levels of salivary nickel and chromium do not increase after the installment of orthodontic appliances. Material and methods: However, there are no studies on salivary levels of titanium, cobalt, copper and zinc in these patients. Salivary levels of nickel (Ni), titanium (Ti), chromium (Cr), cobalt (Co), copper (Cu) and zinc (Zn) were measured in 42 patients with ceramic brackets and in 42 patients with metal conventional brackets prior to insertion of orthodontic appliances and six months after insertion of orthodontic appliances by means of inductive coupled plasma/mass spectrometry. Statistical analysis was performed by use of Wilcoxon signed rank test and Mann Whitney test with level of significance set at 0.05. Results: The results showed that salivary level of titanium increased significantly six months after installment of orthodontic appliances. Salivary level of chromium and zinc significantly decreased after installment of orthodontic appliances. There were no significant differences in salivary levels of nickel, titanium, chromium, copper, cobalt and zinc between the patients with metallic and those with ceramic brackets. Conclusion: We might conclude that the salivary level of titanium increased significantly six months after installment of orthodontic appliances unlike salivary levels of chromium and zinc which significantly decreased after installment of orthodontic appliances, regardless of bracket type which was used.